Site-specific integration by adeno-associated virus. - Kotin, R M (1990)
Cellular sequences flanking integrated copies of the adeno-associated virus (AAV) genome were isolated from a latently infected clonal human cell line and used to probe genomic blots derived from an additional 21 independently derived clones of human cells latently infected with AAV. In genomic blots of uninfected human cell lines and of primary human tissue, each flanking-sequence probe hybridized to unique bands, but in 15 of the 22 latently infected clones the flanking sequences hybridized not only to the original fragments but also to a total of 36 additional species. AAV probes also hybridized to 22 of these new bands, representing 11 of the 15 positive clones, but never to the fragment characteristic of uninfected cell DNA. From these data we conclude that the AAV genome preferentially integrates into a specific region of the cellular genome. We have determined that the integration site is unique to chromosome 19 by somatic cell hybrid mapping, and this sequence has been isolated from uninfected human DNA.